CEREBELLUM AND COGNITIVE PROCESSES - Nieto Barco, Antonieta; Engeby, Tone Wollman; Barroso Ribal, José (Anales de Psicología / Annals of Psychology, 2004)
Cerebellum has long been regarded as involved in the control and coordination of movement. Since the mid-1980s, a number of anatomical, neuroimaging, and clinical studies have provided evidence that the cerebellum participates in various higher level cognitive processes. This paper reviews the data in support of this idea.